Frequency of Hepatitis B in Thalassemia Major Patients - Hussain, Akber; Malik, Qudrat Ullah; Ikram, Farooq; Ullah, Naeem; Nadeem, Muhammad Tariq; Hussain, Murtaza (Journal of Rawalpindi Medical College, 2023)
Background: Thalassemia is a set of inherited hematological illnesses caused by mutations in the genes that code for globin. Regular blood transfusions extend the lives of thalassemia patients, but they also increase the danger of blood-borne illness infections. Objective: The current study was conducted to check the frequency and risk factors of hepatitis B virus (HBV) infections among β thalassemia major patients. Methods: The study was conducted over a period of 3 months that is from November 2021 to February 2022 in the department of Thalassemia center CMH Rawalpindi. The study consists of thalassemia patients aged 6 months to 15 years including both male and female patients. Their venous blood was taken and transmitted to the laboratory, Armed force institute of pathology CMH Rawalpindi, for hepatitis B surface antigen test (HbsAg). Their demographic information was gathered, including their age, gender, number of blood transfusions received each year and Hepatitis B virus (HBV) vaccination status. Results: Out of 100 patients there were 45 patients who were male and 55 patients who were female. The patients’ ages span from 6 months to 15 years, with a mean age difference of 11.20 years and a standard deviation of 5.56. In three months, the mean difference in the number of blood transfusions received by patients was 22.7 6.6 SD. Patients under the age of ten were 50 percent of the time, and patients beyond ten were also 50 percent of the time (50 percent). Five (5%) of the total 100 patients tested positive for hepatitis B. In three months, the mean difference in the number of blood transfusions received by patients was 18.2 5.6 SD. Thirty (30%) patients out of a total of 100 were not immunized. Conclusion: Frequency of hepatitis B in beta thalassemia major patients is minimal (less than 5 per 100) is seen in our study. To reduce the future risk of TTI, development of strong national and regional policies on safe blood transfusion procedures, VNRD-based transfusions, and universal quality-assured donor screening are recommended.